Effect of Mass and Contact Time of Coffee Grounds in Nickel Metal Ion Adsorption on Liquid Waste of Chemistry Laboratory - Trinanda, Inez; Yussi Pratiwi; Tritiyatma Hadinugrahaningsih (Chemistry and Materials, 2025)
Based on Indonesian Government Regulation PP No. 22 of 2021 concerning the implementation of environmental protection and management, the quality standard for nickel in waters is 0.05 mg/L. Nickel waste is very harmful to aquatic and terrestrial ecosystems and poses risks to human health. In this study, nickel waste was treated with coffee grounds using the adsorption method. The purpose of this study was to determine the effect of variations in the mass of coffee grounds and contact time on the adsorption of nickel metal in the liquid waste generated by the UNJ Chemistry laboratory. Coffee grounds are activated with NaOH 0.01 M to increase their adsorption ability. Two tests were conducted, namely, the variation of adsorbent mass and the variation of contact time. Based on the results of testing the variation of adsorbent mass and contact time, the highest percentage of removal was obtained at 91.70% at a mass of 0.05 g with a contact time of 15 minutes. The lowest percentage of removal was 39.56% in a mass of 1.5 g with a contact time of 90 minutes. This research provides a novel approach to heavy metal waste treatment especially nickel metal ion, which can be adapted to enhance waste treatment technologies in the future.